Changing dynamics of the nuclear energy policy‐making process in Japan. (29th October 2020) - Kikuchi, Masao
Abstract: To improve the effectiveness of environmental policy and governance, recent theoretical and empirical research increasingly suggests the adoption of multi‐level and more participatory policy‐making processes over traditionally centralized policy‐making processes. This article takes the Fukushima nuclear crisis of 2011 as a prime example in an attempt to assess the changing dynamics of the nuclear energy policy‐making process in Japan. To explore the changing dynamics, the paper focuses on the roles of the judicial branch and local governments in the nuclear energy policy‐making process. Nuclear energy policy in Japan has evolved along with industrial policies for economic growth. Before the Fukushima crisis, neither the judicial branch nor local governments were regarded as influential actors in nuclear energy policy‐making. The judicial branch basically supported government policy in litigation brought by civic groups. Local governments in rural areas tried to attract nuclear power plant construction because of promised subsidies from the national government and a solid tax base from construction and jobs. However, after the Fukushima crisis, both judicial branches and local governments became more influential in the nuclear energy policy‐making process. Local and high courts now actively issue injunctions against the reoperation of nuclear power plants. In gubernatorial or mayoral elections of local governments where nuclear power plants are located, candidates are politically pressured to express their stance on nuclear power plants more explicitly than in the past. Anti‐nuclear civic groups are also gradually changing the focus of their lobbying efforts to local elections.